English brainstormers! ready-to-use games and activities that make language skills fun to learn - Umstatter, Jack.; Umstatter, Maureen (San Francisco, Calif : Jossey-Bass, 2002)
Useful for English and language arts teachers in grades 6-12, this book is a collection of over 180 ready-to-use activities that help build the skills your students need for test-taking and overall academic success.
Keywords: English language -- Study and teaching (Secondary) -- Activity programs; English language -- Study and teaching (Middle school); Activity programs; Word games